HISTORY OF MARKETS, HISBAH AND ITS IMPLEMENTATION IN THE ERA OF THE PROPHET SAW UNTIL MODERN TIMES - Muhammad Naufal Mukhtar; Khusnudin Khusnudin (Nurul Jadid University, 2024)
Abstract This study aims to explore the historical development and contemporary implementation of hisbah—the Islamic institution of market supervision—from the era of Prophet Muhammad SAW to the modern context. Employing a qualitative approach through historical-normative library research, this study analyzes primary sources including the Qur'an, Hadith, and classical Islamic texts, as well as secondary data from scholarly journals, books, and institutional reports. The research focuses on the conceptualization of markets in Islam, the establishment of hisbah as a regulatory institution, and its transformation in response to modern economic governance. Findings reveal that the Islamic market, as structured by the Prophet SAW, was founded on principles of justice, transparency, and public welfare, with hisbah functioning as a moral safeguard against fraud, exploitation, and market distortion. The role of the muhtasib (market inspector) historically ensured ethical compliance in economic transactions. In contemporary times, while formal hisbah institutions have diminished, their ethical foundations are echoed in various regulatory bodies such as consumer protection agencies and Islamic financial authorities. This research contributes to Islamic economic literature by reaffirming the relevance of hisbah in modern economic systems and highlighting the need for ethical reintegration in market policies. The study suggests further empirical research on the institutional adaptation of hisbah values in different national contexts to support the development of equitable and morally grounded market systems.